VOLUNTARY DISCLOSURES OF HUMAN RESOURCE MANAGEMENT IN THE COVID-19 PANDEMIC FINANCIAL REPORTING ERA OF CONSUMER AND INDUSTRIAL GOODS FIRMS LISTED ON THE NIGERIA EXCHANGE GROUP (Journal of Global Accounting, 2022)
The paper focuses on voluntary disclosures of human resources management in the financial reports of publicly listed consumer goods and the industrial goods firms during the Covid-19 pandemic era. Specifically, it intends to determine the level of effect that voluntary disclosures of Human Resource Management (HRM) of sampled firms during the COVID-19 pandemic era has on personnels’ productivity. The consumer goods and industrial goods sector were the focus of this study. Twenty (20) consumer goods companies and thirteen (13) industrial goods companies listed on the Nigerian Exchange Group were sampled. Data were analyzed using multiple regression analytical technique. The study found out that voluntary disclosures of Human Resource Management (HRM) of sampled firms during the COVID-19 pandemic era has a strong and positive significant effect on personnels’ productivity (p-value .000 < 0.05; t-statistics 5.098). Based on these outcomes, the study advised that disclosures of Human Resource Management should be made mandatory and enforced accordingly in order to improve on the attitude of organizations to issues of Human Resource Management knowing fully well that the pandemic affected human resources more than the other resources of the companies such as materials and machines. Hence, the number of pages allotted by companies in their Financial Statements for Human Resource Management disclosures should be increased to allow for more extensive disclosures of HRM practices during the year under coverage. This is visibly a positive impression that all contributions of the companies’ human resources are valued and  very much important, not just to the management and the Board but to the Shareholders in general.
Keywords: Financial Reporting practices; Human Resource Management; Personnels’ productivity; Total Equity; Voluntary disclosures